Spiral Pumping Wheel Turbine Application Concept for Irrigation with Different Altitudes - Anas Mukhtar; Gatut Rubiono (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2022)
One of the problems of irrigation on agricultural land is the lower position of irrigation water sources. Pumps are needed to raise water to the planting area. Water pumps that are widely sold in the market generally require electrical energy so that their operation requires a source of electricity and operational costs. Spiral pump wheels can be applied because this wheel utilizes the flow of water to pump water without the need for electrical energy. The purpose of this article is to describe the concept of a spiral pumping wheel application for irrigation at different heights. The description is done with simple technical drawings to explain how the wheel works. This description of how it works provides an overview of the mechanisms that occur when this type of wheel is applied. The description is also equipped with aspects of material selection, manufacturing methods and performance aspects. Modifications for increasing the performance of the wheel are also described. An application example is given in the form of a photo of conditions in the field as an additional explanation. A description of the application of the spiral pump wheel has been carried out and is expected to be a reference for the application of this device in the community.